Epidemiological Aspects, Clinical Features and Treatment Outcome in Children Suffering Hepatoblastoma - Mohajerzadeh, Leily; Faraji , Nooshin; Khaleghnejad Tabari, Ahmad; Rouzrokh , Mohsen; Ghoroubi , Javad; Shamsian , Shahin (Iranian Journal of Pediatric Surgery, 2021)
Introduction: Hepatoblastoma (HBL) is the most common primary liver tumor within childhood. Entire tumor resection is basis for ultimate cure for HBL and supports the only pleasant chance of long-standing disease-free survival. Objectives: In the current survey, we attempted to evaluate the long-term survival of children with HBL with surgical resection in a referral children hospital in Iran within the last decade. Materials and Methods:This retrospective descriptive study was conducted on all children who suffered HBL and undergone surgery between 2006 and 2016. Reviewing the recorded hospital files led to a sample of 30 eligible patients. The baseline characteristics of the patients were all collected by reviewing the files. Results:In total, 30 consecutive children (21 male and 9 female) suffering HBL were described. Of those, 40.0% aged less than 12 months and only 6.7% aged higher than 36 months. The most common clinical manifestations were asymptomatic abdominal mass (in 66.7%) followed by fever (in 10.0%) and pain (in 10.0%). In more than half of the patients (53.3%), right lobe involved, while left lobe involved in 16.7%. based on histologicalreport,marginal involvement was found in 75.0% of children, margin intact in 15.0% and margin free feature in 5.0%. Forty percent of children suffered from epithelial subtype of tumor, 20.0% from mixed epithelial and mesenchymal subtypes, and 13.3% from embryonal pattern. In total, 63.3% were scheduled for complete surgical resection followed by chemotherapy. Postoperatively, 40.0% of children remained free of complications, whereas postoperative bleeding occurred in 20.0% and biloma in 40.0%. Overall, 76.9% of patients were completely cured, 7.7% suffered from pulmonary metastasis and 3.9% required liver transplantation. Postoperative death occurred in 11.5%. Conclusions: Considering surgical resection followed by chemotherapy leads to high cure rate, however a notable number of affected children suffer postoperative complication, requiring liver transplantation, pulmonary metastasis, or even non-survived emphasizing a serious review of the treatment protocols.